PELATIHAN PENULISAN KARYA ILMIAH MELALUI PELAKSANAAN PTK BAGI GURU SDN ANAK AIR KECAMATAN KOTO TANGAH PADANG - Yahya Yahya; Yusro Wikarya; Eswendi Eswendi (Ranah Seni, 2019)
The problem is prioritized to the main interrelated aspects, namely the problem: (1) the inability of teachers to understand and apply scientific writing in their writings, and (2) the inability of teachers to understand and write PTK proposals. Problem solving is done by approaching: (a) the design of teaching materials, (b) counseling, and (c) training. The activity has produced: (a) teaching material of scientific writing material, CAR concept, and the process of writing a CAR proposal, (b) as much as 74.12% scientific writing material, 72.35 CAR concept material, and 70.59% proposal writing process material PTK has been mastered by the participants, and (c) the knowledge has been applied by partner teachers in writing proposals